2023
DOI: 10.1097/moo.0000000000000874
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implant in tinnitus management

Abstract: Purpose of reviewTo evaluate whether cochlear implantation can mitigate tinnitus perception and its discomfort among patients with severe-to-profound hearing loss, in order to provide an answer on a possible treatment for a health condition with high prevalence and impact on quality of life. Recent findingsTinnitus can develop after peripheral hearing loss and is associated with altered auditory processing. It does not only involve auditory structures but also aberrant neural activity and interaction with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Therapeutic approaches using electrical stimulation of the cochlea to reduce tinnitus perception have been developed since the 1970s [9,10]. In addition, numerous studies that have analyzed the effects of cochlear implants (CI) on tinnitus have found them effective in reducing tinnitus loudness [11][12][13][14]. However, despite the evidence that CI can reduce tinnitus, it is unclear whether the reduction is achieved by counteracting peripheral deafferentation [15], electrical stimulation via an implanted electrode [16], or by the interaction of both.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic approaches using electrical stimulation of the cochlea to reduce tinnitus perception have been developed since the 1970s [9,10]. In addition, numerous studies that have analyzed the effects of cochlear implants (CI) on tinnitus have found them effective in reducing tinnitus loudness [11][12][13][14]. However, despite the evidence that CI can reduce tinnitus, it is unclear whether the reduction is achieved by counteracting peripheral deafferentation [15], electrical stimulation via an implanted electrode [16], or by the interaction of both.…”
Section: Introductionmentioning
confidence: 99%